Kualitas Layanan Peminjaman Buku pada Perpustakaan Akademik Melalui Pendekatan SERVQUAL: Studi Persepsi Mahasiswa - Eka Aulia Syafitri; Farel Mauzia Hidayat; Ayu Dwi Septiana; Nadila Jalianti; Naila Rasyifa Zahra Arofik; Joko Tri Nugraha (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to examine and understand the quality of book lending services in the academic library based on students’ experiences and perceptions as service users. The quality of library services is a crucial factor that influences student satisfaction and engagement with academic resources. This research uses a descriptive quantitative approach with the SERVQUAL method, which evaluates service quality across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through questionnaires distributed to 95 students selected using random sampling, then analyzed using validity tests, reliability tests, and descriptive statistics to identify response patterns. The results show that, in general, the book lending service is categorized as good. This is indicated by the dominance of “agree” and “strongly agree” responses given by respondents across most indicators. In addition, the research instrument has been proven to be valid and reliable, meaning the data obtained are consistent and reflect the actual service conditions. This condition occurs because several aspects of the service, such as the ease of the borrowing process and the attitude of the staff, have met students’ expectations. However, some aspects remain suboptimal, particularly book availability, the borrowing system, and operational hours, resulting in uneven levels of satisfaction among students. Practically, this study implies that library managers should prioritize continuous and targeted improvement in the underperforming service dimensions to ensure that service quality becomes more evenly distributed and better meets the diverse needs of all students